Copper-catalyzed cascade reactions of α,β-unsaturated esters with keto esters - Li, Zhengning (Beilstein J Org Chem, 2015)
A copper-catalyzed cascade reaction of α,β-unsaturated esters with keto esters is reported. It features a copper-catalyzed reductive aldolization followed by a lactonization. This method provides a facile approach to prepare γ-carboxymethyl-γ-lactones and δ-carboxymethyl-δ-lactones under mild reaction conditions.